Volumetric and viscometric studies on electrolytes in non-aqueous solvent (Daffodil International University Journal of Science and Technology, 2010)
The densities, ρ and viscosities, η of NH4Cl, NiCl2 and FeCl3 in dimethylsulfoxide were studied as a function of concentration. The partial molal volume, (φ0v) of these electrolytes were evaluated. The viscosity and viscosity-coefficients (A and B) were also determined by Jones-Dole equation. B-coefficient for NiCl2 and FeCl3 are positive that show structure making behavior in all the solutions while those of NH4Cl are negative indicating structure breaking properties. The coefficient A represents the solute-solute interactions coupled with size and shape effect of the solute and to some extent solute-solvent interactions. The behaviors of three solutes in binary systems were discussed in terms of the charge, size and hydrogen bonding effect. Keywords: Density, Apparent and partial molal volume, viscosity coefficient. DOI: 10.3329/diujst.v4i2.4360 Daffodil International University Journal of Science and Technology Vol.4(2) 2009 pp.15-18